2020
DOI: 10.1029/2019jg005347
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Foliar Nutrient Status and Stoichiometry to Nitrogen Addition in Different Ecosystems: A Meta‐analysis

Abstract: Atmospheric nitrogen (N) deposition alters the cycling of nutrients in terrestrial ecosystems. However, there is limited knowledge regarding how N addition affects foliar nutrients beyond N and phosphorus (P) and their stoichiometry. We conducted a meta‐analysis, including 2,004 observations from 134 fertilization studies, to synthesize the effects of N addition on multiple foliar nutrients and stoichiometry in terrestrial ecosystems and to examine their potential controls. Overall, we found that N addition si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 81 publications
(159 reference statements)
2
20
1
Order By: Relevance
“…Consistent with our first hypothesis, we found that N addition increased Mn concentrations in green shoots for most of the eight examined species after 6 years. Our results are contrast with the results from a meta‐analysis which reported no impacts of N addition on foliar Mn concentration averaged across diverse ecosystems (Mao et al., 2020), but are quite similar with results from other temperate steppe of northern China (Tian et al., 2016, 2021). The Mn concentrations in green shoots varied significantly among different plant species in this temperate steppe.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Consistent with our first hypothesis, we found that N addition increased Mn concentrations in green shoots for most of the eight examined species after 6 years. Our results are contrast with the results from a meta‐analysis which reported no impacts of N addition on foliar Mn concentration averaged across diverse ecosystems (Mao et al., 2020), but are quite similar with results from other temperate steppe of northern China (Tian et al., 2016, 2021). The Mn concentrations in green shoots varied significantly among different plant species in this temperate steppe.…”
Section: Discussioncontrasting
confidence: 54%
“…In a meta‐analysis based on 134 studies, Mao et al. (2020) reported no impacts of N addition on foliar Mn concentration. Tian et al.…”
Section: Introductionmentioning
confidence: 99%
“…The restriction of other elements caused by nitrogen enrichment further counteracts the positive effect of nitrogen increase on plant growth (Wang et al 2018;Zhan et al 2019). Phosphorus (P) is an essential element for plant energy transmission and growth (Baldarelli et al 2021;Falkowski et al 2000), while potassium (K) can not only improve the uptake and utilization of nitrogen, but also enhance the resistance of plants (Deng et al 2017;Hooper and Johnson 1999;Mao et al 2020;Vitousek et al 2010). Human disturbance (such as deforestation and fertilization) leads to soil erosion and acidi cation, which in turn leads to loss of available P and K from plants to eutrophication of rivers and lakes (Cloern 2001;Conley 1999;Rader and Richardson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [25] and Scott et al [26] found that the nutrients status in the decomposition environment could influence the decomposition rates and nutrient dynamic of plant litter. The addition of nitrogen (N) could decrease the ratio of carbon to nitrogen (C/N) and phosphorus (P) concentration, thus accelerating the decomposition of litter [29][30][31]. Similarly, several studies have reported that the P enrichment in water could increase the P concentration and reduce the ratios of carbon to phosphorus (C/P) and nitrogen to phosphorus (N/P) in litter [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…To test these hypotheses, we studied the variation of litter mass and nutrient dynamic during the decomposition process. The decomposition rate (K) of litter, derived from the negative exponential model proposed by Olson [47], is used to show the speed of decomposition after a period of time [31,48]. Previous study has reported that decomposition rate could not indicate the integrity of decomposition and the effects of environmental factors on the whole decomposition process [49].…”
Section: Introductionmentioning
confidence: 99%